2020
DOI: 10.3390/ma13163506
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Visible Light Active WO3 Thin Films Toward Air Purification: Effect of the Synthesis Conditions

Abstract: Taking our current environmental situation in the world into consideration, people should face growing problems of air and water pollution. Heterogeneous photocatalysis is a highly promising tool to improve both air and water quality through decomposition/mineralization of contaminants directly into harmless CO2 and H2O under ambient conditions. In this contribution, we focused on the synthesis of self-assembly WO3 thin films via an electrochemical approach in the aqueous electrolyte containing fluoride ions t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 63 publications
1
3
0
Order By: Relevance
“…The recorded PL spectra for all PEO-processed Al samples under investigation in this study are shown in Figure 10. The PL spectra feature a pronounced spectral maximum at 500 nm, most probably originating from WO 3 [27,28]. The PL intensity follows the same order as the photocatalytic activity, which was also correlated with the W content observed from the EDS results.…”
Section: Photocatalytic Activity and Photoluminescence Of The Peo Coa...supporting
confidence: 70%
“…The recorded PL spectra for all PEO-processed Al samples under investigation in this study are shown in Figure 10. The PL spectra feature a pronounced spectral maximum at 500 nm, most probably originating from WO 3 [27,28]. The PL intensity follows the same order as the photocatalytic activity, which was also correlated with the W content observed from the EDS results.…”
Section: Photocatalytic Activity and Photoluminescence Of The Peo Coa...supporting
confidence: 70%
“…In this study, the photocatalytic activity was the highest when the oxide layer thickness was about 2 µm. Appropriate oxide layer thickness is beneficial to the movement of photogenerated electron-hole pairs and improves photocatalytic activity, as has been discussed [46]. Also, it has been discussed that the fabrication of unique structures with specific exposed crystal facets provides an excellent platform for WO 3 PEC performance tuning [11].…”
Section: Photoelectrochemical Measurementsmentioning
confidence: 98%
“…The most intense UV emission band of the WO3 NSs was observed at a lower wavelength of 362 nm than that of the ZnO NSs (378 nm). However, other emission bands were observed in the visible spectral range, covering violet (411 nm), blue (453 and 487 nm), and green (523 nm) emission bands [62]. The emission bands observed in the blue-green spectral region (453 and 487 nm) lie in the same energy range as the WO3 bandgap (~2.8 eV).…”
Section: Photoluminescence Emission Behavior Of Zno-wo 3 Hybrid Ncsmentioning
confidence: 92%